The Influence of Ship Services on the Revenue of PT. Port of Indonesia (Persero) Regional 1 Dumai Branch - Evada Rustina; Dandi Pratama; Jaya Wisana; Lidyawati Moiyo; Dwi Endaryanti; Edwina Nur Utami (Meteor STIP Marunda, 2023)
Dumai Port is an important port in Riau, which supports Riau's economy. PT. Pelabuhan Indonesia I Dumai Branch is a branch of PT. Pelabuhan Indonesia I Medan, a company engaged in port services. This study aims to find out whether there is an influence of domestic and foreign ship services on the income of PT. Port of Indonesia (Persero) Regional 1 Dumai branch and find out how much the number of domestic and foreign ship services contributes to the revenue of PT. Port of Indonesia (Persero) Regional 1 Dumai Branch. This study uses a quantitative research methodology, a data analysis tool using simple linear regression with the application of SPSS. The results of the study show that based on the calculation of simple linear regression, it can be seen that the correlation level of 0.875 or 87.5% means that the influence of the number of ship services on the revenue of PT. The Port of Indonesia (Persero) Regional 1 Dumai branch is very strong, and the degree of coefficient relationship of 0.70 – 0.90 is a medium relationship or a moderate influence. Based on the calculation of the determination coefficient (R2), it was found that the results obtained a value (R2) of 0.766 or 76.6%, meaning that the ship service variable was able to provide an influence with a contribution of 76.6% to the revenue of PT. Port of Indonesia ( Persero ) Regional 1 Dumai branch.